Metaphors used in advertising language and their semantic load - Kilicheva Mekhriniso Radjabovna,; Utkirova Shakhnoza Abbos kizi, (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2026)
The role of metaphors in advertising language occupies a special place in linguistics, pragmatics, and marketing research. Metaphor is actively used not only as a means of artistic expression but also as a communicative and persuasive instrument. In advertising texts, metaphors are used to influence the consumer's consciousness, form a brand image, and intuitively explain the characteristics of the product. In this regard, a deep analysis of metaphors in advertising language helps to understand the semantic, pragmatic, and cultural aspects of language.